Enhanced dielectric properties of Ba3ZnTa2−xNbxO9 in microwave region using tungstic acid. (2nd January 2020) - Tomar, Richa; Bisht, Yogita; Abhilash, Pullanchiyodan; Thirumal, Meganathan
ABSTRACT: Dielectric resonators belonging to the families of complex perovskite Ba3 ZnTa2− x Nb x O9 were synthesized by a solid-state reaction route. Calcination at 1250°C leads to oxides with ordered (hexagonal) perovskite structure over the range (0.25 ≤ x ≤ 1.75). However, ordering refraction intensity of PXRD patterns increased on sintering at 1340°C with tungstic acid, as a sintering aid. Sintering has lead to >90% density. In microwave range, Ba3 ZnTa0.5 Nb1.5 O9 shows much higher permittivity (35) and quality factor (43, 120 GHz).